Evaluation and comparison of three methоds оf DNA extractiоn frоm Kazakh horse of the type Zhabe - Kabylbekova, D.I.; Khamzina, Zh.; Aubakirova, K.P.; Ibadullayeva, A.A. (Karagandy University of the name of acad. E.A. Buketov, 2023)
Horse breeding is one of the main directions in the livestock industry of Kazakhstan. Horse breeding is an economically important part of breeding, as horses have a high productive value. The purpose of this article was to determine the most optimal from the point of view of economic efficiency of the scientific DNA isolation method for genotyping of the Kazakh horse. In this study, we performed the first step (DNA extraction) in genotyping the DNA of the Kazakh horse to further determine the signs of growth, meat and dairy productivity. Nowadays, new generation sequencing technologies have made scientific and technological progress in research. Obtaining highly concentrated and non-contaminated DNA is the main stage of successful analysis. For further genetic studies, a concentration of 50 ng/ml is required, which is considered minimal. In the study, three different DNA extraction methods from tissue were subjected to comparative analysis in order to evaluate and identify the most effective DNA extraction method from horse ear tips. Real-time PCR amplification based on gel electrophoresis and spectrophotometric measurements (Nano Drop) were used to evaluate the isolated DNA's quality and quantity. In addition, energy consumption, time, as well as the cost of analysis were evaluated. According to the obtained results, extraction using the commercial kit protocol was simple to use, effective, but relatively expensive. The phenol-chloroform and CTAB methods are the same in terms of DNA quality, but given the danger of the phenol component used in the phenol-chloroform method, the CTAB method turned out to be the most acceptable for genotyping, because it is safe, not expensive and effective.
Қазақтың бақа басты жылқысының түрін ДНҚ экстракциялаудың үш түрлі әдісін салыстыру және бағалау
Оценка и сравнение трех методов экстракции ДНК у казахской лошади типа жабе
Keywords: horse breeding; Kazakh horse; Zhabe; PCR; phenol-chloroform method; CTAB method; genotyping; DNA extraction; electrophoresis